Hexahelix Analysis: Accelerating Food Loss and Waste Management in Support of Circular Economy Implementation in the Local Region - Octavianto, Said Nur; Amin Pujiati; Sucihatiningsih Dian Wisika Prajanti (Department of Development Economics, Universitas Sriwijaya, 2024)
The substantial amount of food waste generated in Sragen Regency due to inadequate food loss and waste (FLW) management has a detrimental impact on the environment. This study aims to analyze the efforts to optimize FLW management, examine the relationships between variables, and assess stakeholder synergy in accelerating FLW management to support the implementation of a circular economy in the Sragen Regency. This research employs a mixed-methods approach, with data analysis conducted using MICMAC and MACTOR methodologies. The MICMAC analysis results indicate that stakeholder relationships, waste prevention, location factors, cultural factors, and community scale are the core variables for accelerating improvements in FLW management. In contrast, the MACTOR analysis identifies the Environmental Agency (DLH), Kecik Waste Bank, and Si Repi Waste Bank as the primary stakeholders in these efforts. Additionally, the MACTOR analysis highlights changes in community behavior and the utilization of FLW in the circular economy as primary objectives agreed upon by all stakeholders. The findings from the MICMAC and MACTOR analyses provide a basis and reference for determining the model and grand design of an FLW management acceleration strategy to support the implementation of a circular economy in the Sragen Regency.